Tissue engineering of human hair follicles using a biomimetic developmental approach - Abaci, Hasan Erbil; Coffman, Abigail; Doucet, Yanne; Chen, James; Jacków, Joanna; Wang, Etienne; Guo, Zongyou; Shin, Jung U.; Jahoda, Colin A.; Christiano, Angela M. (Nature Communications, 2018)
Human skin constructs (HSCs) have the potential to provide an effective therapy for patients with significant skin injuries and to enable human-relevant drug screening for skin diseases; however, the incorporation of engineered skin appendages, such as hair follicles (HFs), into HSCs remains a major challenge. Here, we demonstrate a biomimetic approach for generation of human HFs within HSCs by recapitulating the physiological 3D organization of cells in the HF microenvironment using 3D-printed molds. Overexpression of Lef-1 in dermal papilla cells (DPC) restores the intact DPC transcriptional signature and significantly enhances the efficiency of HF differentiation in HSCs. Furthermore, vascularization of hair-bearing HSCs prior to engraftment allows for efficient human hair growth in immunodeficient mice. The ability to regenerate an entire HF from cultured human cells will have a transformative impact on the medical management of different types of alopecia, as well as chronic wounds, which represent major unmet medical needs.
EPrint Processing Status: Full text deposited in DRO